Dampak strategi membaca digital, dialogis, dan tradisional terhadap keterampilan bahasa, pemahaman cerita, dan penalaran kausal: Studi komparatif - Ria Candra Dewi (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2026)
The purpose of this study was to investigate the comparative impact of three strategies, namely digital reading, dialogic reading, and traditional reading, on students' receptive and expressive language skills, story comprehension, and causal reasoning abilities. A quasi-experimental method was used involving 252 students aged 7—11 years. The instruments used were assessments of language skills, story comprehension, and causal reasoning. Descriptive data analysis and the Wilcoxon signed-rank test were used in this study. The research findings showed that language skills (receptive and expressive), story comprehension, and causal reasoning in the dialogic reading group showed the most significant improvement compared to the digital reading and traditional reading groups. Improvements in receptive language skills were seen in the ability to listen to stories critically and use new vocabulary. Improvements in story comprehension skills were seen in the level of plot understanding. Causal reasoning skills were seen in the ability to analyze causality between events in the story. Improvements in all skills occurred because the dialogic scaffolding (open, semi-open, and prompting questions) encouraged students to continue thinking critically and actively express their ideas.